Impaired adrenergic agonist‐dependent beige adipocyte induction in aged mice. Issue 2 (27th December 2016) - Shin, Woongchul; Okamatsu‐Ogura, Yuko; Machida, Ken; Tsubota, Ayumi; Nio‐Kobayashi, Junko; Kimura, Kazuhiro
Abstract : Objective: There are two types of thermogenic adipocytes expressing uncoupling protein (UCP)−1: the brown adipocyte activated by adrenergic stimulation and the beige adipocyte that appears within the white adipose tissue (WAT) in response to chronic adrenergic stimulation. This study examined age‐related changes in responses of both types of adipocytes to adrenergic stimulation in mice. Methods: Aged (age 20 months) and young (4 months) mice were injected daily with either saline or β3‐adrenergic receptor agonist CL316, 243 (CL; 0.1 mg/kg, once a day) for 1 week. Results: The body and WAT weight tended to be higher in aged mice. CL treatment increased UCP‐1 protein amounts in both brown adipose tissue and inguinal WAT, suggesting activation of brown and beige adipocytes. However, induction of beige adipocytes was impaired in aged mice, whereas brown adipocyte activation was comparable to young mice. The number of platelet‐derived growth factor receptor α‐expressing progenitor cells, which were reported to differentiate into beige adipocytes, significantly decreased in inguinal WAT of aged mice compared with that of young mice. Conclusions: Inductive ability of beige adipocytes in WAT declines with aging in mice. It may be partly because of a decreased number of progenitor cells associated with aging.